Group Counselling and Psychotherapy with Childre and Adolescents : Theory, Research, Practice - Zipora Shechtman (New York Routledge)
Many children and adolescents face developmental or situational difficulties in areas where they live most of their meaningful experiences-at home, at school, and in the community. While adults who struggle with life events and stressors may look to professional help, young individuals are quite alone in coping with these situations. Perhaps unsurprisingly, most children and adolescents typically do not seek such help, and often resist it when offered.
Keywords: Psychology